MENELAAH WAKTU TERJADINYA RESIKO ( KEHILANGAN / KERUSAKAN BARANG ) DALAM PRAKTIK PROSES PENGANGKUTAN LAUT - Alfian Nanung Pradana dan Rizki Nur Annisa, Adnandaka Nurvigya (GEMA, 2015)
In some of sale purchase contract that involving parties from different region separated by oceans, the sea transport will be an option for the business people. In the sea transport, the risks in exists in several laws, one of which is in article 40 Law Number 17 Year 2008 about the cruise. Phase in the process of transporting allows the difficulty in proving to determine where the risks occur. These things often happen in restuffing phase and destuffing phase in the loading port and be intentional negligence on the part of the seller of shipper.